Object and Subject of Crime in Contemporary Criminal Law: Doctrinal Evolution, Judicial Practice, and Theoretical Reassessment - Aleksandr M. Voronin (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2026)
The object and subject of crime constitute foundational categories of criminal law theory, shaping the understanding of criminal liability, the structure of corpus delicti, and the qualification of criminal acts. Despite their long-standing presence in legal doctrine, these concepts remain among the most debated and methodologically complex in both continental and post-Soviet criminal law traditions. This article undertakes an extensive theoretical and doctrinal analysis of the object and subject of crime, tracing their historical evolution from classical criminal law thought to modern interpretations under conditions of market relations, information society, and evolving judicial practice. Drawing strictly on authoritative doctrinal works, judicial resolutions, and comparative theoretical materials reflected in the provided references, the study elaborates the internal structure of the object of crime, its correlation with social relations, legal goods, and interests protected by criminal law, as well as the multifaceted understanding of the subject of crime as a material or immaterial bearer of criminal encroachment. Particular attention is paid to Soviet and post-Soviet scholarly debates, including disagreements over the distinction between object and subject, their role in the mechanism of criminal harm, and their significance for crime qualification. The article also examines special categories such as information, securities, symbols, and victims, demonstrating how technological and socio-economic transformations challenge traditional doctrinal boundaries. Judicial interpretations, including those of supreme courts, are analyzed to illustrate the practical implications of theoretical positions. The study argues for a nuanced, integrative approach that preserves doctrinal continuity while accommodating contemporary realities. By synthesizing classical theory, modern scholarship, and judicial practice, this article contributes to a deeper understanding of the object and subject of crime as dynamic legal categories essential for coherent criminal law doctrine and effective law enforcement.